Analysis of The Relationship Between Financial Fraud Losses and Market Factors - Liu, Xinwei (Transactions on Economics, Business and Management Research, 2024)
As digital financial services continue to expand, so too does the complexity of financial fraud schemes, affecting both individuals and large corporations. Despite economic growth and increased government attention, the incidence of fraud has not significantly decreased. This study, informed by the Agency Theory of Michael Jensen and William Meckling and Keynesian Economics, investigates the relationship between financial fraud amounts and key market factors such as market volatility, regulatory strength, economic environment, GDP growth rate, and unemployment rate. Through a quantitative analysis of historical data, the study aims to understand how these factors influence the occurrence and scale of financial fraud. Preliminary results indicate a significant correlation only with regulatory strength, suggesting that robust regulatory measures may be crucial in combating fraud. However, the absence of strong correlations with other factors hints at a more complex interplay that warrants further exploration, indicating the need for a nuanced understanding of the dynamics at play in financial fraud.